Jicama Seed Response After Administering Auxiliary Hormones and Gibberellins - Mulyanti; Dewi Yana; Lukman Martunis (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Plant growth and development is influenced by hormones, which are chemical compounds that are synthesized in a part of the organs that are distributed to the organs, and play a special role at low doses or are slightly able to stimulate plant growth, development and metabolic processes. One of the plants that need growth regulators or hormones for growth and development is Jicama. The aim of the study was to see the response of jicama seeds after administration of auxin and gibberellin hormones. This study used a factorial Randomized Block Design (RBD), namely the first factor of the Auxin hormone with levels A0 = 0 ml, A1 = 1 ml, A2 = 2 ml. The second factor is the Gibberellin hormone with a level of G0 = 0 ml, G1 = 1 ml, G2 = 2 ml. All treatments were repeated 5 (five) times to obtain 45 experimental units. The results of the study showed that the auxiliary hormone and gibberellins and the combination of the two hormones had a very significant effect on live sprouts and shoot height.